2003
DOI: 10.1177/014556130308200812
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Telithromycin for 5 or 10 Days vs Amoxicillin/Clavulanic Acid for 10 days in Acute Maxillary Sinusitis

Abstract: Telithroniycin (HMR 3647) is a new ketolide antimicrobial that was developed for the treatment ofcommunityacquired respiratory tract infections. We conducted a randomized, double-blind, multicenter study to compare the clinical efficacy and safety of oral telithromycin; at 800 mg once dail yfor 5 or 10 days, with that ofamoxicillin/ clavulanic acid, at 500/125 mg three times daily for 10 days, in adults with acute maxillary sinusitis (AMS). A total of 754 patients with AMS of less than 28 days' duration were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 17 publications
3
40
0
2
Order By: Relevance
“…[60][61][62][63][64][65][66][67][68][69] AECB More than 6% of US adults have AECB. 70 Approximately 50% of exacerbations are caused by typical bacteria (ie, S pneumoniae, H influenzae, and M catarrhalis).…”
Section: Capmentioning
confidence: 99%
“…[60][61][62][63][64][65][66][67][68][69] AECB More than 6% of US adults have AECB. 70 Approximately 50% of exacerbations are caused by typical bacteria (ie, S pneumoniae, H influenzae, and M catarrhalis).…”
Section: Capmentioning
confidence: 99%
“…The bacteriological results were supported by the clinical efficacy data, which demonstrated that the 5-day regimen of telithromycin is as effective as 10-day regimens of telithromycin and two currently available comparators, amoxicillin-clavulanic acid and cefuroxime axetil. In addition, the individual studies from which data for the current pooled analysis were taken showed that telithromycin was as effective as either comparator alone; the clinical efficacy rates observed in these studies were: telithromycin (5 days) 74.1% versus amoxicillin-clavulanate (10 days) 74.5% [29] and telithromycin (5 days) 85.2% versus cefuroxime-axetil (10 days) 82.0% [27]. Previous studies have demonstrated that telithromycin has high activity in vitro against S. pneumoniae [16,[18][19][20][21][22][23] and also exhibits concentration-dependent bactericidal activity against this pathogen [21].…”
Section: Discussionmentioning
confidence: 91%
“…In these trials, a 5-day course of oral telithromycin 800 mg administered once daily was compared with a 10-day course of oral telithromycin (Study 3002) [28], a 10-day course of oral telithromycin or a 10-day course of oral amoxicillin-clavulanic acid 500/125 mg three-times daily (Study 3005) [29], and a 10-day course of oral cefuroxime axetil 250 mg twice daily (Study 3011) [27]. In a pooled analysis, the bacteriological and clinical efficacy of 5 days' therapy with telithromycin was evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations